Molecular dynamic simulation: Structural insights of multi-stranded curdlan in aqueous solution. (1st June 2021) - Feng, Xuan; Li, Fan; Ding, Mingming; Zhang, Ran; Shi, Tongfei; Jiang, Wei
Graphical abstract: Highlights: Right-hand triple helix is thermodynamically the most stable conformation The triple helix is stabilized by the inter-strand HB network from C2 hydroxyls O2 −HO2 HBs present a left-handed double helix with global orientation preferences The formation of triple helix is sensitive to temperature but the maintenance is not DP6 may be a critical chain length to form the triple helix conformation Abstract: In this work, by using molecular dynamic simulation we provide microscale structure information which helps to reveal the molecular mechanisms concerning the multi-chain conformational behavior of short curdlan. Through simulations starting with different conformations of curldan dodecasaccharides, it is found that the right-handed triple helix is thermodynamically the most stable conformation in aqueous solutions, which is well maintained and stabilized by an inter-strand hydrogen bonding network of the C2 hydroxyls. Unlike any predicted forms, the inter-strand hydrogen bonds exhibit a left-handed double helix pattern with preferred global orientations. Temperature REMD results suggest that the formation of triple helix is temperature sensitive, but the already formed triple helix is not. Investigation of curdlan with numbers of repeating units from 3 to 12 captures a critical value of 6, which in a way elucidates the relationship between the formation of triple helix and the chain length.